Prevalence of epidemiological influence, risk factors of type-2 Diabetes Mellitus and analysis of hypertension as a complication among the relatively newly diagnosed patients from BIRDEM hospital - Chowdhury, Ishtiak Ahmed (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.